2002
DOI: 10.1292/jvms.64.551
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Liver Proliferative Lesions in Heterozygous p53 Deficient CBA Mice to Various Carcinogens.

Abstract: ABSTRACT. To investigate the liver tumorigenic sensitivity to various carcinogens in heterozygous p53 deficient [p53 (+/-)] CBA mice and their wild-type littermates [p53 (+/+) mice], 71 p53 (+/-) and 74 p53 (+/+) CBA mice (male, 6-12 weeks of age) were given diet containing 4,000 or 0 ppm flumequine (FL) for 26 weeks or a single intraperitoneal injection of 5 mg/kg body weights dimethylnitros amine (DMN) at start of the study in Exp. 1, diet containing 6,000 or 0 ppm di(2-ethylhexyl)-phthalate (DEHP) for 26 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…An earlier study showed that about 2 mg/kg/day dose of NDMA to C3H/He mice for 32 days causes promutagenic DNA lesion (O 6 -methylguanine) [ 17 ]. In a study, CBA mice were subjected to a single dose of NDMA (5 mg/kg) and kept the animals for 26 weeks but any apparent hepatocellular tumor was not observed [ 18 ]. In a liver fibrosis study, ICR strains of mice were subjected to 8 mg/kg dose of NDMA for 15 days at regular intervals (totaling 120 mg/kg) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study showed that about 2 mg/kg/day dose of NDMA to C3H/He mice for 32 days causes promutagenic DNA lesion (O 6 -methylguanine) [ 17 ]. In a study, CBA mice were subjected to a single dose of NDMA (5 mg/kg) and kept the animals for 26 weeks but any apparent hepatocellular tumor was not observed [ 18 ]. In a liver fibrosis study, ICR strains of mice were subjected to 8 mg/kg dose of NDMA for 15 days at regular intervals (totaling 120 mg/kg) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous 26-week study in which DEHP or PhP was administered to each male p53 (+/-) and p53 (+/+) mice, hepatocellular altered foci were detected in the control animals. The incidence of this type of lesion in the control p53 (+/-) mice receiving DEHP was approximately 22%, while the incidences of the same type of lesion in the control p53 (+/-) and p53 (+/+) mice receiving PhP were approximately 33 and 26%, respectively 11 . In addition, Takizawa et al (2003) reported that focal necrosis of hepatocytes occurred in control p53 (+/+) mice in a 26-week study administering KA 10 .…”
Section: Discussionmentioning
confidence: 88%
“…Smith et al (1973) reported that the spontaneous incidences of lymphoma in CBA mice were 6% in males and 15% in females of CBA strain 12 . In our previous 26-week study using p53 (+/-) and p53 (+/+) mice, a dead animal due to malignant lymphoma was found during the treatment period 11 . Furthermore, the incidences of death were not dose-dependent in the present study, therefore, these deaths were considered not to be attributable to the KA treatment.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, activating mutations in the β-catenin gene are thought to be responsible for the excess β-catenin signaling featured in the majority of carcinogen-induced colonic lesions 67 , including small foci 68 . Mammary carcinogenesis induced by DMBA 16 and hepatocarcinogenesis initiated with the genotoxic carcinogens dimethylnitrosamine (DMN), 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP), 6-nitrochrysene (6-NC) 69 , 2-amino-3,8-dimethylimidazo[4,5-f]quinoxaline (MeIQx) 70 , DEN 15 , and other chemicals 71 including APNH, a novel heterocyclic amine 19 , may reflect organ/tissue specificity in the threshold for the p53 gene product. While the mechanism may involve an additional hit to inactivate the second normal allele, Venkatachalam et al 55 have proposed that reduction of the p53 gene products may be sufficient to promote tumorigenesis.…”
Section: P53 (-/-) Mice Are Most Sensitivementioning
confidence: 99%